A CRISPR-based base-editing screen for the functional assessment of BRCA1 variants - Kweon, Jiyeon (Oncogene, 2019)
Genetic mutations in BRCA1, which is crucial for the process of DNA repair and maintenance of genomic integrity, are known to increase markedly the risk of breast and ovarian cancers. Clinical genetic testing has been used to identify new BRCA1 variants; however, functional assessment and determination of their pathogenicity still poses challenges for clinical management. Here, we describe that CRISPR-mediated cytosine base editor, known as BE3, can be used for the functional analysis of BRCA1 variants. We performed CRISPR-mediated base-editing screening using 745 gRNAs targeting all exons in BRCA1 to identify loss-of-function variants and identified variants whose function has heretofore remained unknown, such as c.-97C>T, c.154C>T, c.3847C>T, c.5056C>T, and c.4986+5G>A. Our results show that CRISPR-mediated base editor is a powerful tool for the reclassification of variants of uncertain significance (VUSs) in BRCA1.